2017
DOI: 10.3389/fmicb.2017.00288
|View full text |Cite
|
Sign up to set email alerts
|

RNA Primer Extension Hinders DNA Synthesis by Escherichia coli Mutagenic DNA Polymerase IV

Abstract: In Escherichia coli the highly conserved DNA damage regulated dinB gene encodes DNA Polymerase IV (DinB), an error prone specialized DNA polymerase with a central role in stress-induced mutagenesis. Since DinB is the DNA polymerase with the highest intracellular concentrations upon induction of the SOS response, further regulation must exist to maintain genomic stability. Remarkably, we find that DinB DNA synthesis is inherently poor when using an RNA primer compared to a DNA primer, while high fidelity DNA po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…We used 90- or 180-bp dsDNAs and ssDNAs of varying lengths of homology (from the heterologous N = 0 up to N = 98) and a total length of 98 nt. For polymerase, we used either 1 μ m Escherichia coli DNA Pol IV (obtained using Pol IV overproducer plasmids (31, 32)) or 5 units of DNA LF- Bsu Pol (New England Biolabs; 5000 units/ml). DNA Pol IV reactions were done in RecA buffer containing 0.1 mg/ml BSA, 2 m m dATP, and 0.4 m m dNTPs, whereas DNA LF- Bsu Pol experiments were performed in RecA buffer containing 1 m m ATP and 30 m m NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…We used 90- or 180-bp dsDNAs and ssDNAs of varying lengths of homology (from the heterologous N = 0 up to N = 98) and a total length of 98 nt. For polymerase, we used either 1 μ m Escherichia coli DNA Pol IV (obtained using Pol IV overproducer plasmids (31, 32)) or 5 units of DNA LF- Bsu Pol (New England Biolabs; 5000 units/ml). DNA Pol IV reactions were done in RecA buffer containing 0.1 mg/ml BSA, 2 m m dATP, and 0.4 m m dNTPs, whereas DNA LF- Bsu Pol experiments were performed in RecA buffer containing 1 m m ATP and 30 m m NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Escherichia coli Pol IV was purified from the TMCΔT strain (BL21-AI ΔdinB, ΔumuDC, ΔrecA) by ion exchange chromatography and hydrophobic interaction chromatography as previously described (30,31). Oligonucleotides were obtained from Integrated DNA Technologies (IDT) and are listed in the Supplementary Materials and Methods section.…”
Section: Methodsmentioning
confidence: 99%
“…In normally growing cells, Pol IV was shown not to contribute to the error rate of chromosomal DNA replication (Kuban et al, ; Wolff et al, ), most likely due to limited access to the normal replication fork. Tashjian et al () have shown in vitro that DinB performs poor DNA synthesis with RNA primers and that it is additionally impeded upon interaction with RecA. They postulate that poor synthesis of DinB using RNA primers might represent a mechanism to prevent DNA synthesis by DinB when it is not needed.…”
Section: Tls Polymerasesmentioning
confidence: 99%